Developing and Introducing Evidence Based Clinical Practice Guidelines for Serious Illness in Kenya - Irimu, Grace (2008)
The under-5 mortality rate in most developing countries remains high yet many deaths could be averted if available knowledge was put into practice. For seriously ill children in hospital investigations in low-income countries commonly demonstrate incorrect diagnosis and treatment and frequent prescribing errors. To help improve hospital management of the major causes of inpatient childhood mortality we developed simple clinical guidelines for use in Kenya, a low-income setting. The participatory process we used to adapt existing WHO materials and further develop and build support for such guidelines is discussed. To facilitate use of the guidelines we also developed job-aides and a 5.5 days training programme for their dissemination and implementation. We attempted to base our training on modern theories around adult learning and deliberately attempted to train a ‘critical mass’ of health workers within each institution at low cost. Our experience suggests that with sustained effort it is possible to develop locally owned, appropriate clinical practice guidelines for emergency and initial hospital care for seriously ill children with involvement of pertinent stake holders throughout. Early experience suggests that the training developed to support the guidelines, despite the fact that it challenges many established practices, is well received, appropriate to the needs of front line health workers in Kenya and feasible. To our knowledge the process described in Kenya is among a handful of attempts globally to implement inpatient or referral care components of WHO / UNICEF’s Integrated Management of Childhood Illness approach. However, whether guideline dissemination and implementation result in improved quality of care in our environment remains to be seen.